Company Value Through Company Size As A Moderating Variable: Intellectual Capital, Inventory Turnover, Return Of Assets - Saputra, Deni; Yudha , Agam Mei; Yamasitha, Yamasitha (Yayasan Bina Internusa Mabarindo, 2024)
This research aims to determine the influence of intellectual capital, inventory turnover, and return on assets on company value with company size as a moderating variable (case study of the LQ 45 company in 2018-2022). intellectual capital, inventory turnover, and return on assets are used as independent variables and firm value is used as the dependent variable. And company size as a moderating variable. This research was conducted at the LQ45 company. The sample used in this research was LQ45. The data used is secondary data. The analytical method used is multiple regression analysis. The analytical tool used is SPPS 25. The research results obtained are based on the partial test: there is a positive and significant influence of intellectual capital on company value, there is a negative and insignificant influence of inventory turnover on company value, there is a positive and significant influence of return of assets on company value , company size is able to moderate the influence of intellectual capital on company value, company size is not able to moderate the influence of inventory turnover on company value. Company size is able to moderate return of assets on company value.